Acute myelitis with hyperIgEaemia and mite antigen specific IgE: atopic myelitis - Kira, J. (BMJ Group, 1998)
An occurrence of acute localised myelitis was recently seen in four adult patients with atopic dermatitis who had hyperIgEaemia and mite antigen specific IgE. The total and mite antigen specific IgE was therefore studied in serum samples from 19 consecutive patients with acute localised myelitis of unknown aetiology, 56patients with clinically definite multiple sclerosis, and 40 healthy controls. The total IgE concentration was significantly higher in acute localised myelitis (median=360 U/ml) than in multiple sclerosis (median=52 U/ml, p<0.0001) and the controls (median=85 U/ml, p=0.0002). The specific IgE to Dermatophagoides pteronyssinus was found more often in patients with acute localised myelitis (95%) than in patients with multiple sclerosis (34%, p<0.0001) and the controls (35%, p<0.0001) and the specific IgE to Dermatophagoides farinae was similar (acute localised myelitis 79%, multiple sclerosis 29% (p<0.0001), controls 30%, (p=0.0003). Atopic dermatitis coexisted more commonly in patients with acute localised myelitis (37%) than in patients with multiple sclerosis (0%, p<0.0001) and the controls (7.5%, p=0.0089). Therefore, acute localised myelitis with hyperIgEaemia, in which atopy to mite antigens seems to exist, may be a distinct subtype of allergic myelitis—that is, atopic myelitis.